The myths surrounding pre-exercise carbohydrate feeding - Jeukendrup, A. E.; Killer, S. C. (Annals of Nutrition and Metabolism, 2010)
Carbohydrate ingested 30-60 min before exercise may result in hypoglycaemia during exercise, a phenomenon often called rebound or reactive hypoglycaemia. There is considerable confusion regarding pre-exercise carbohydrate feeding with advice that ranges from `consume carbohydrate in the hour before exercise` to `avoid carbohydrate in the 60 min prior to exercise`. Methods: We analysed the studies available in the literature to draw conclusions about the use of carbohydrate in the pre-exercise period. Results: Without performing a meta-analysis, it is clear that the risk of reduced performance is minimal as almost all studies point towards unaltered or even improved performance. This is despite the rather large metabolic changes that occur in response to pre-exercise carbohydrate feeding. Conclusion: It can be concluded that advice to avoid carbohydrate feeding in the hour before exercise is unfounded. Nevertheless athletes may develop symptoms similar to those of hypoglycaemia, even though they are rarely linked to actual low glucose concentrations. An individual approach may therefore be necessary to minimize these symptoms even though they do not appear to be related to exercise performance.